The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1515/jpme.1998.26.5.371
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of polyhydramnios in the third trimester in a population screened by first and second trimester ultrasonography

Abstract: In this study, the prevalence of polyhydramnios in the third trimester was lower than in previous studies, as well as being associated with a better prognosis. This may have been the result of a combination of several factors. These include the introduction of multi-level ultrasound screening for fetal abnormality, and the improved care of diabetic women, and mothers with rhesus iso-immunisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…It causes the decrease production of amniotic fluid by increase absorption of fluid by lungs, reducing the urine output and also impairs the prostaglandin mediated response of renal vasculature 7,10,11 . The frequency of polyhydramnios was 1.7% in our study which corresponds with the other study mentioned in literature which showed the incidence of 1-2% respectively [2][3][4][5][6] . The causes of polyhydramnios in our study was mainly idiopathic which was similar to study performed by Maymon et al 12 , Tariq S et al 13 and Panting Kemp et al 14 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It causes the decrease production of amniotic fluid by increase absorption of fluid by lungs, reducing the urine output and also impairs the prostaglandin mediated response of renal vasculature 7,10,11 . The frequency of polyhydramnios was 1.7% in our study which corresponds with the other study mentioned in literature which showed the incidence of 1-2% respectively [2][3][4][5][6] . The causes of polyhydramnios in our study was mainly idiopathic which was similar to study performed by Maymon et al 12 , Tariq S et al 13 and Panting Kemp et al 14 .…”
Section: Discussionsupporting
confidence: 90%
“…Polyhydramnios is one of the dreaded complication in obstetric practice, as it affects not only mother but also the fetus. The overall incidence is 1-2% [2][3][4][5][6] . It causes maternal complications like antepartum hemorrhage, respiratory embarrassment, abnormal presentation, uterine dysfunction and also postpartum hemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“…Phelan et al described quantification of amniotic fluid using the amniotic fluid index (AFI). 8 The four-quadrant technique termed AFI is in which a vertical pocket of amniotic fluid, free of umbilical cord, in each of four equal uterine quadrant was summated. An amniotic fluid volume more than two standard deviation below the mean for specific gestational age or volume reduced below the 5th percentile for particular gestational age would define oligohydramnios.…”
Section: Research Articlementioning
confidence: 99%
“…Finally, 20% of polyhydramnios cases are related to diabetes. 3,12 Because polyhydramnios in such pregnancies is not considered idiopathic, those pregnancies were excluded from other studies and their outcome is not clear.…”
mentioning
confidence: 99%